2018
DOI: 10.1097/corr.0000000000000523
|View full text |Cite
|
Sign up to set email alerts
|

Is a Cephalomedullary Nail Durable Treatment for Patients With Metastatic Peritrochanteric Disease?

Abstract: Background Although cephalomedullary nail fixation is often used for metastatic peritrochanteric lesions of the femur, there is concern regarding the durability of the implant in comparison to endoprosthetic reconstruction. Previous studies have reported the proportion of patients who undergo reoperation for loss of stability, but the adequacy of the construct has not been critically evaluated in a competing risk analysis that incorporates death of the patient in the calculation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…In the trochanteric region, intramedullary nails (IM-nails), conventional prostheses or tumour prostheses can be used. As complications related to non-union and tumour growth such as implant breakage and loosening tend to occur 6-12 mo postoperatively, in patients with a shorter estimated survival (3-6 mo), IM-nailing is adequate[ 10 , 12 , 35 , 36 ]. However, IM-nails should not be used if there is tumour mass affecting the neck of the femur, even if the fracture itself is in the intertrochanteric region.…”
Section: Methods and Outcome Of Surgical Treatmentmentioning
confidence: 99%
“…In the trochanteric region, intramedullary nails (IM-nails), conventional prostheses or tumour prostheses can be used. As complications related to non-union and tumour growth such as implant breakage and loosening tend to occur 6-12 mo postoperatively, in patients with a shorter estimated survival (3-6 mo), IM-nailing is adequate[ 10 , 12 , 35 , 36 ]. However, IM-nails should not be used if there is tumour mass affecting the neck of the femur, even if the fracture itself is in the intertrochanteric region.…”
Section: Methods and Outcome Of Surgical Treatmentmentioning
confidence: 99%
“…Previous literature demonstrated that hormone-receptor positive patients have a higher risk of having bone metastatic disease, but concomitantly these same patients also tend to have a better prognosis, with better treatment response and longer overal survival [9] , [28] , [29] , [13] , [14] . Earlier studies have shown that the most important factor for bone fixation failure was the length of the patient’s survival [30] , [31] . In accordance with this, our data showed that patients with metastic breast cancer treated with intramedullary rods required a late revision with a mean time for the revision procedure of 19.4 months.…”
Section: Discussionmentioning
confidence: 99%
“…This study had a number of limitations. First, our sample was of a relatively reduced size, with a total of 57 patients, and even though this was the biggest sample we found in the literature regarding specifically metastatic breast cancer and its treatment exclusively with intramedullary rodding, we acknowledge we did not have enough power to achieve significance in our results [30] , [20] . For the difference in revision rate among the different groups, 12% vs. 17%, our study attained to show a trend in the association between hormone receptors and rod survival, unfortunately those numbers did not reach statistical significance and our sample size likely played a role in that.…”
Section: Limitationsmentioning
confidence: 99%
“…In several of the small cohort studies on metastatic bone disease of the femur we reviewed, the methods suggested that a chart review for data abstraction took place, but it was unclear if or how the chart review contributed to the definition of eligible patients. 12 13 14 15 16 , 18 - 20 , 25 …”
Section: Discussionmentioning
confidence: 99%
“… 17 Some studies have used the CPT and ICD codes to define cohorts of patients with metastatic disease of the femur, 17 whereas others do not explicitly state the criteria or methodology that were used to identify patient cohorts. 12 13 14 15 16 , 18 - 20 Efforts to produce studies with larger sample sizes will likely rely on structured data to identify patient cohorts. A lack of understanding of the characteristics and accuracy of cohorts defined by ICD and CPT codes could lead to biased conclusions.…”
mentioning
confidence: 99%